Avaliação do estado nutricional da mangueira Tommy Atkins irrigada no Vale do Açu em diferentes épocas de amostragem foliar - Araújo, Júlio Justino de (Universidade Federal Rural do Semi-Árido, 2010)
The nutritional evaluation through foliate analysis has become a useful tool to nutritional analysis in several cultures around the world. Although, there are different methods to interpret foliate analysis, there seems to be a few studies about the utilization of the diagnosis and recommendation integrated system (DRIS) and about the methodology of critical level for the reduced and normal distribution (NCRIZ), to evaluate the nutritional state of irrigated mango tree Tommy Atkins. The objective of this work is evaluating the nutritional state of the mango tree in the valley of Baixo Açu in two different seasons of foliating samplings, using DRIS and NCRIz methodologies to identify and put in order the nutritional limitations and compare the methodologies. The work was developed in Vale do Açu, an important mango tree producer in the state of Rio Grande do Norte, mainly in fluvial neo-soils. The samplings were chemically analyzed during the mango tree fenological development based on N, P, K, Ca, Mg, S, B, Zn, Mn, Fe and Cu contents, and respective productivities were collected in 106 cuts supplied by mango exportation companies. To determine the DRIS, the rules, calculation of the DRIS and the nutritional balance for each element and their relation two by two were established. To determine the critical level (NCRIZ), a developed method which uses normal distribution or Gauss-Laplace type was chosen. It is based on continuous distribution of reduced probability. To calculate the critical level, P equals to 90% of maximum production. The methodologies DRIS and NCRIZ were proved efficient to identify the limiting nutrients for the mango tree, once there are differences about limitation hierarchical order. As rules DRIS showed differences about the low productivity population. The variations will probably represent the level of limiting nutrients by excess and deficiency, whereas the NCRIZ allowed to calculate the levels within the reference recommended by the bibliographical referential. Thus, it is another tool for nutritional diagnosis having the advantage of no experiments in the field
Evaluation of the nutricional state of Tommy Atkins mango tree irrigated in the Valley of the Açu at different times of sampling
Keywords: Manga; Análise foliar; Nutrição de plantas; Avaliação do estado nutricional; Mango; Foliate analysis; Plants nutrition; Nutritional situation evaluation; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA::ENGENHARIA DE SOLO E AGUA::IRRIGACAO E DRENAGEM